Social Justice and the European Green Deal : Green transition in a well-ordered society - Maunuksela, Oskari (My University, 2024)
The European Union (EU) is an intergovernmental supranational union of 27 member countries located in Europe. The union has claimed global leadership in addressing environmental problems such as greenhouse gas emissions (GHGs), pollution and habitat loss. In late 2019, a key European Union actor, the European Commission, released a new program to tackle both economic and environmental challenges, named the “European Green Deal” (EGD). Although the EGD is mostly an economic program, it contains major implications for both environmental and social justice. The focus of this thesis is to analyse those fields of justice through the theoretical framework proposed by John Rawls, known as “Justice as Fairness” or a Theory of Justice. Special emphasis is put on social justice and policy resilience. Aspects of the Green Deal are also contextualised to their wider context of just green transitions, a subfield of environmental ethics. There is a special focus on stability and resilience, and the EU is seen analysed in relation to the Rawlsian ideal of a well-ordered society. Policy stability and resilience over the long term are seen as important especially due to the long lifespan of the EGD program (from 2020 -2050). Many of the hallmarks of the Rawlsian theory, mainly its emphasis on securing basic liberties and advancing social equality are also taken into account. The European Union can be regarded on most aspects as a Rawlsian well-ordered society. Among the key findings of this thesis is that as a mostly economic dossier, many of the aspects of social justice are absorbed in the EGD program. Another reason for absorbing social justice is the institutional structure of the EU: the proposer of the EGD, the European Commission, is not in charge of social policies, as those mostly lay in the power of the EU member states. Social justice is still visible in the EGD, for example, in the stated goal of “not leaving anyone behind”, and instruments such as “Just Transitions Mechanism” and “Carbon Border Adjustment Mechanism”. It can be claimed that the social justice implications of the EGD enhance both ecological and social resilience of the program and increase policy stability and success through an appeal to shared values. The Rawlsian theoretical framework, and especially his theory of “justice as fairness” are found to provide a practical analytical basis for a work of political philosophy as the one found in this thesis.
Keywords: John Rawls, European Green Deal, political philosophy, just green transition, resilience, ecological justice, social justice, European Union